A History of God : From Abraham to the Present, the 4000 Year Quest for God - Armstrong, Karen (London Mandarin, 1995)
The idea of a single divine being - God, Yahweh, Allah- has existed for over 4000 years. In this account of the evolution of belief Armstrong examines Western society's unerring fidelity to this idea of one God and the many conflicting convictions it engenders. Originally published in 1993 by William Heinemann.
Include Glossary, Notes, Bibliography and Index.
Keywords: God--History of doctrines -- God -- God--Biblical teaching -- God (Islam)--History of doctrines -- God (Judaism)--History of doctrines -- Islam--Doctrines -- Judaism--Doctrines -- Social conflict--Religious aspects